2001
DOI: 10.1093/humrep/16.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with ICSI of infertility caused by azoospermia associated with adrenal rests in the testes: Case report

Abstract: Congenital adrenal hyperplasia (CAH) is a well-recognized, but uncommon, cause of azoospermia and infertility in men. Commonly this is due to undertreatment of excessive adrenal androgen secretion which suppresses gonadotrophin stimulation of the testes. A less common complication of CAH is development of adrenal tissue within the testes; this is important to recognize because it may be confused with malignancy leading to unnecessary surgery. In this case report, a man is described with simple virilizing CAH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
20

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 31 publications
2
27
0
20
Order By: Relevance
“…One relatively common form of gonadal abnormality in affected males is the development of testicular adrenal rests, detectable by sonographic imaging before they become palpable (Stikkelbroeck et al 2001). Such tumours have been detected even in childhood (Murphy et al 2001), suggesting that the search for them should begin no later than adolescence. In males with salt wasting, testicular rest tissue may be accompanied by deficient spermatogenesis despite treatment.…”
Section: Reproductive Functionmentioning
confidence: 99%
“…One relatively common form of gonadal abnormality in affected males is the development of testicular adrenal rests, detectable by sonographic imaging before they become palpable (Stikkelbroeck et al 2001). Such tumours have been detected even in childhood (Murphy et al 2001), suggesting that the search for them should begin no later than adolescence. In males with salt wasting, testicular rest tissue may be accompanied by deficient spermatogenesis despite treatment.…”
Section: Reproductive Functionmentioning
confidence: 99%
“…The testicular tumours, which are always located in the mediastinum testis, can lead to obstruction of the vascular supply and compression and atrophy of the seminiferous tubules. In addition to these mechanical effects, steroids produced by the tumours could be toxic to testicular tissue (paracrine effect) therefore contributing to testicular failure 15 . These two factors result in primary gonadal failure with elevated gonadotropin levels and low inhibin Β levels.…”
Section: Testicular Adrenal Rest Tumoursmentioning
confidence: 99%
“…Although controversial (14,15), male infertility has been described in patients with 21-hydroxylase deficiency. Regarding the underlying mechanism of male infertility in 21-hydroxylase deficient patients, suppression of gonadotropin secretion by increased adrenal steroids due to the untreated deficiency is considered to be the cause of spermatogenesis failure (16), while it has also been suggested that the main cause of infertility in such patients is the presence of testicular adrenal rest tumors, thought to originate from aberrant adrenal tissue (17), which compress the seminiferous tubules, causing obstructive azoospermia (18). In the present two cases, though low serum concentrations of LH and FSH were observed, neither steno-sis nor compression of seminiferous tubules by a testicular tumor was identified, which supports the speculation that the suppression of gonadotropin by increased adrenal androgens due to untreated 21-hydroxylase deficiency may result in sperm dysfunction (19).…”
Section: Discussionmentioning
confidence: 99%